Apllication of Ovaprim and Oxytocin Hormone for Gonadal Maturation and Embryogenesis of the Pomfret (Colossoma mropomum) - Mustahal Mustahal; Mas Bayu Syamsunanrno; Ariq Dwi Wijanarko (Jurnal Perikanan dan Kelautan, 2020)
The pomfret fish have been widely cultured by fish culturist in Indonesia. However, the gonadal maturation have faced the obstacles with the hormone supplies for the culturists. Therefore, the purpose of this study was to determine the dose of ovaprim and the oxytocin hormone in accelerating gonadal maturation as well the embryogenesis of  the pomfret fish by semi-natural spawning methods. The study was conducted from September to November 2019 at the Laboratory of Fish Seedling Production, at  Baros District, Serang Regency. The number of fish used was 18 fishes (12 males and 6 females), for each spawning treatment have been used 2 males and 1 female. The experiments were using a completely randomized design (CRD) consisting of 2 combinations of treatments and 2 replications. The treatments used were as follows: 0.5 ml / kg ovaprim (K), 0.5 ml / kg ovaprim + 0.25 ml / kg oxytocin (P1), 0.25 ml / kg ovaprim + 0.25 ml / kg oxytocin (P2). The results showed that the use of combination of ovaprim and oxytocin (P1 and P2) was able to stimulate the maturity and spawning of the pomfret fish. The oxytocin injection to induce the spawning have been increased the latency time and increased the fecundity of the pomfret fish. The best hormonal combination treatment in resulting the gonadal maturation and egg hatching was that of  the P2 with the fastest latency time was 614.50 ± 13.44 minutes, the fecundity was 460,134 ± 72,597, fertilization rate  was 80.28 ± 3.11% and hatching rate was 77.08 ± 0.16%.